A BIM-IoT and intelligent compaction integrated framework for advanced road compaction quality monitoring and management. (May 2022) - Han, Tao; Ma, Tao; Fang, Zhou; Zhang, Yang; Han, Chengjia
Abstract: The road construction industry is undergoing a continuous digital transformation due to higher construction quality control and management requirements to improve efficiency and reduce cost consumption. IC (Intelligent compaction) is an emerging and developing technology that can overcome the limitations of current quality control and quality assurance approaches, such as detection hysteresis and incompleteness. However, IC is mainly used in a vehicle system to realize real-time quality inspection, while its further potential is not fully exerted in advanced construction control and management as a comprehensive, continuous and nondestructive testing tool. This paper proposes a BIM (Building Information Model)-IoT (Internet of things) and IC integrated framework to provide a fundamental platform for advanced compaction quality monitoring and management. Specifically, BIM provides high-fidelity virtual assets of road infrastructure for data integration, visualization and construction organization management. IC is used to provide comprehensive compaction quality monitoring data and quality control methods. IoT (Internet of things) is adopted to connect physical and cyber assets by capturing real-time data from the actual operations in construction. Finally, a prototype system is developed as an implementation of the framework. The case demonstration of the system shows that the proposed framework can effectively integrate BIM and IC to realize the monitoring of road compaction quality and data in combination with IoT data, and the construction schedule can be rearranged and optimized based on the monitoring results. This study can facilitate to realize road compaction quality real-time monitoring and management, as well to offer a basic BIM-IoT platform that can be utilized as a prototype of road infrastructure digital twin to achieve more intelligent and sustainable management of the entire construction process in the future.